Aggregation induced by the synergy of sodium chloride and high-pressure improves chlorophyll stability. (1st January 2022) - Li, Fangwei; Zhou, Liang; Cao, Jiarui; Wang, Zhenhao; Liao, Xiaojun; Zhang, Yan
Highlights: The synergy of NaCl and high-pressure improves food color stability was first posed. The relationship between the synergy and Chl aggregation was first described. Quantum chemical calculations and experiment were combined to explain the mechanism. The synergy markedly increased the Chl retention, and the increase rate reached 100%. Abstract: The development of green vegetable processing is still limited by the imperfect green protection now. Chlorophyll (Chl), the main pigment presented in green vegetables, was studied that the effects of NaCl on the stability of it, and the synergy of NaCl and high-pressure on Chl protection. Compared to the control, the retention of Chl was increased by 80.14% and the activation energy was 62.7% higher in 7.8% NaCl solution. When the pressure was 600 MPa with 7.8% NaCl, the synergy of NaCl and high-pressure increased the Chl retention by 100%. The restriction of NaCl to H2 O provided Chl with a lower polarity environment and increased the contact between Chl molecules. And the fluorescence quenching confirmed the aggregation of Chls induced by high-pressure. This study explains the mechanism of green protection by NaCl and high-pressure, broadening the horizon for the development of color protection in vegetable processing.